Assessment of stakeholders' preferences towards sustainable sanitation scenarios. (26th June 2012) - Bao, Pham Ngoc; Aramaki, Toshiya; Hanaki, Keisuke
Abstract Decision making in sanitation planning is often complex, with inherent trade‐offs among sociopolitical, environmental, technical and economic factors. The selection of appropriate and sustainable sanitation systems for municipal wastewater treatment involves multiple criteria with conflicting stakeholder preferences. To fulfil conflicting yet complementary objectives, one of the best known and most widely used multi‐criteria analysis (MCA) approaches called the Analytic Hierarchy Process (AHP) has been employed as a decision support tool to aid decision makers in sanitation planning process in developing countries. AHP, in combination with life cycle assessment (LCA) and a proposed set of multidimensional criteria, has worked as an effective decision support tool for the sustainability assessment and selection of appropriate wastewater treatment system with a capacity of 1200 m3/day, in a case study in Toan Thang, a small town in Vietnam. Results from this case study have indicated that the public's understanding of trade‐offs is critical in gaining public support for long‐term sustainability of the solution. The findings from this study have also shown AHP as an effective and flexible communication tool for group decision making in sanitation planning.